Mineralized Allograft Implant Site Preservation in 3-Wall Post-Extraction Sockets in Ten Subjects: Clinical, Radiographic and Histologic Evaluation - Clementini, Marco; Sannino, Gianpaolo (The Journal of Dentists, 2013)
Objective: The purpose of the present investigation was to evaluate the efficacy of a surgical technique using mineralized human allograft and a collagen membrane on counteracting dimensional changes of 3-wall post-extraction socket. Materials and Methods: In 10 patients, 10 single extraction sites without the labial bone plate in the anterior area were treated by means of mineralized human allograft and a collagen membrane. Intraoral radiographs and clinical measurement were taken at baseline and after 4 months. At surgical reentry, prior to implant placement, a biopsy core was obtained for histological analysis. Results: After 4 months of healing the intraoral radiographs showed a mean difference in bone level height of 0.77 mm (SD ± 0.63), while clinical measurements showed a mean reduction of 1.1 mm (SD ± 0.46) in width, allowing for normal diameter implants placement without the need of further augmentation procedures. The specimens harvested showed bone formation, composed of particles of mineral human bone allograft and newly formed bone trabeculae. Conclusion: Alveolar ridge preservation using mineralized human allograft and a collagen membrane allows for preserving height and width of a 3 wall extraction socket, suggesting that it may be useful prior to dental implant placement, especially in the esthetic region.